Associations between muscle mass, physical activity and dietary behaviour in adolescents. Issue 3 (17th September 2018) - Hao, G.; Pollock, N. K.; Harris, R. A.; Gutin, B.; Su, S.; Wang, X.
Summary: Background and objectives: Investigations in older individuals suggest that adequate nutrition and physical activity are particularly important to skeletal muscle health; however, data in adolescents are scant and equivocal. The objective was to determine the associations among diet, physical activity and skeletal muscle mass in adolescents. Methods: We assessed diet with four to seven 24‐h recalls and physical activity by accelerometry in 640 adolescents. Using total body measures of fat‐free soft tissue mass and fat mass assessed by dual‐energy X‐ray absorptiometry, the skeletal muscle mass index (SMMI) was derived by adjusting fat‐free soft tissue mass for fat mass in addition to height. Results: Skeletal muscle mass index (SMMI) was negatively associated with consumption of sugar‐sweetened beverages (standardized beta coefficient [β] = −0.10, P  = 0.001) and saturated fats (β = −0.28, P  < 0.001). SMMI was positively associated with physical activity (moderate + vigorous) (β = 0.20, P  < 0.001). In further analysis, we observed a significant interaction between physical activity and sugar‐sweetened beverage intake on SMMI ( P  = 0.002). Conclusion: Our study in adolescence suggests that physical activity and consumption of both sugar‐sweetened beverages and saturated fats are associated with skeletal muscle mass. More importantly, our findings suggest that sugar‐sweetened beverage intake may attenuate the beneficial effects of physical activity on skeletal muscle mass.